Design of a broadband microwave rectifier from 40 MHz to 4740 MHz using high impedance inductor - Defu Wang; Renato Negra (2014 Asia-Pacific Microwave Conference, 2014)
This paper proposes a novel configuration of the rectifier which is realised using a high impedance inductor. It removes the input matching network concerning the trade-off of the efficiency and bandwidth. The rectifier with better than 40 % efficiency is designed and measured across the frequency band from 40 MHz to 4740 MHz. The peak RF-DC conversion efficiency of 60.3 % is achieved at 1 GHz operating frequency with 23 dBm incident power. In addition, a minimum of 2 V output DC voltage and greater than 40 % efficiency with 5 dB input power dynamic range from 20 dBm to 25 dBm is obtained covering the entire band.